Yeast telomerase is specialized for C/A-rich RNA templates - Förstemann, Klaus (Oxford University Press, 2003)
Telomeres, the protective caps of eukaryotic chromosomes, are maintained by the enzyme telomerase. This telomere-specific reverse transcriptase (RT) uses a small region of its RNA subunit as template to synthesize telomeric DNA, which is generally G/T rich in the strand that contains the 3′ end. To further our understanding of why telomeres are usually G/T rich, we screened Saccharomyces cerevisiae telomerase RNA (TLC1) libraries with randomized template sequences for complementation of a tlc1 deletion and decapping of existing telomeres. Surprisingly, the vast majority of the 60 000 different mutant telomerase templates tested showed no activity in vivo. This deficiency was not due to impaired assembly with the catalytic subunit (Est2p) nor could it be alleviated by enforced telomerase recruitment to the telomeres. Rather, the mutant templates reduced the nucleotide addition processivity of telomerase. The functional RNA template sequences recovered in our screens preferentially contained two or more consecutive rC nucleotides, reminiscent of the wild-type template. Thus, in contrast to retroviral RTs that can reverse transcribe any RNA sequence into DNA, the budding yeast telomerase RT is specialized for its C-rich RNA template.